An Overview of Retail Sales of Seafood in the USA, 2017–2019. Issue 2 (16th March 2022) - Love, David C.; Asche, Frank; Young, Ruth; Nussbaumer, Elizabeth M.; Anderson, James L.; Botta, Robert; Conrad, Zach; Froehlich, Halley E.; Garlock, Taryn M.; Gephart, Jessica A.; Ropicki, Andrew; Stoll, Joshua S.; et al.
Abstract: While a large number of studies have investigated seafood consumption in various markets, surprisingly little is known about the types of seafood sold in retail outlets or their product forms in the USA. This is particularly true for fresh seafood, which is generally regarded as the most valuable product form of seafood. In this article, a unique dataset on retail in-store seafood sales that includes information about three main product forms (fresh, frozen, and shelf-stable products) was analyzed. Fresh seafood is important, as it makes up 43% of sales revenue. Moreover, some species are almost exclusively sold fresh, with trout and lobster as prime examples. Fresh also includes the greatest diversity of species and, as such, is the most likely product form for new producers to succeed. National sales are dominated by a few species, with salmon and shrimp accounting for a large portion of the fresh (27%) and frozen categories (43%), respectively, and tuna dominating the shelf-stable category (75%). There are also a large number of species with mostly small market shares. There are few differences in regional sales patterns for the main species, with notable exceptions such as whitefish in New England and crawfish in Louisiana and Texas. The degree of urbanization and income level appears as the important drivers for seafood sales. Supplemental data for this article is available online at https://doi.org/10.1080/23308249.2021.1946481